Penerapan Metode Moora dalam Keputusan Pemilihan Produk Layak Produksi Terbaik - Natsir, Fauzan; Izzatilah, Millati; Marsiani, Ega Shela (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2025)
Decision support system is a system that can be a problem solving quickly, especially in ranking and identifying the score of choices from highest to lowest. The research conducted aims to use the MOORA approach in determining superior products, so that it can help companies in the marketing process, selection, and production decisions based on the best product recommendations produced. In this research, the case study discussed is the selection of production-worthy products to meet quality. If the process is still done manually, it takes a long time and the evaluation process becomes inefficient. Therefore, a decision support system was designed to support the evaluation process. The MOORA method is used in the implementation of this system to test its accuracy. The results obtained from this system will be tested through sensitivity tests to criteria, value weighting, and correction tests, with the aim of knowing the number of criteria that can be added.